2008
DOI: 10.1176/ps.2008.59.8.893
|View full text |Cite
|
Sign up to set email alerts
|

Service Utilization Differences for Axis I Psychiatric and Substance Use Disorders Between White and Black Adults

Abstract: Objective Although studies have shown disparities between black and white populations in service utilization for mental disorders, little information exists on whether such disparities apply equally across disorders. The objective of this study was to examine racial differences in lifetime prevalence of service utilization for mood and anxiety disorders and for alcohol and drug use disorders, with controls for predisposing, enabling, and need-for-service variables unequally distributed between racial-ethnic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 78 publications
4
44
0
Order By: Relevance
“…As described by Keyes and others (31), variables that we controlled for the regression model were selected from the Andersen model of health services utilization (32,33). Those confounders consisted of predisposing factors (sex and age) and enabling factors (income, education, marital status, and current insurance status).…”
Section: Methodsmentioning
confidence: 99%
“…As described by Keyes and others (31), variables that we controlled for the regression model were selected from the Andersen model of health services utilization (32,33). Those confounders consisted of predisposing factors (sex and age) and enabling factors (income, education, marital status, and current insurance status).…”
Section: Methodsmentioning
confidence: 99%
“…Those with alcohol dependence before age 30 were unlikely to receive treatment [311], as were Blacks [248], Hispanics [248,312], and women [313,314]. Substance and psychiatric comorbidity predicted treatment [314-317], and equalized black/white differences [318,319]. Medical comorbidity [320], including injury [321] also predicted alcohol treatment.…”
Section: Major Findingsmentioning
confidence: 99%
“…Longer duration and comorbidity predicted treatment [328,329]. Nonwhites were more likely than whites to perceive a need for treatment [328] and to receive treatment [318,319,326,327], often from 12-step groups or clergy [326]. Again, attitudinal barriers were important: participants perceiving a need for treatment were more likely to use services than others, while among participants perceiving a need, those with pessimistic attitudes about treatment outcomes were less likely to use services [330], supporting the need for public education.…”
Section: Major Findingsmentioning
confidence: 99%
“…Most of the diagnosable cases of MDD among Black Americans go untreated and tend to have more impairing effects (Wang et al, 2005;Williams et al, 2007). In terms of professional help-seeking for depression and other mental health problems, research has shown that Black Americans utilize mental health services at a rate below that of Whites (Alegría, Chatterji et al, 2008;Keyes et al, 2008;Williams et al, 2007), even when they have insurance. Despite efforts through the Affordable Health Care Act to increase access to care and establish mental health parity, the overall gap in service use between Blacks and Whites is expected to persist (Alegria, Lin et al, 2012).…”
mentioning
confidence: 99%